2022
DOI: 10.3390/plants11040510
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Circuits in Sap Extracts Reflect the Effects of a Microbial Biostimulant on Maize Metabolism under Drought Conditions

Abstract: The use of microbial biostimulants in the agricultural sector is increasingly gaining momentum and drawing scientific attention to decode the molecular interactions between the biostimulants and plants. Although these biostimulants have been shown to improve plant health and development, the underlying molecular phenomenology remains enigmatic. Thus, this study is a metabolomics work to unravel metabolic circuits in sap extracts from maize plants treated with a microbial biostimulant, under normal and drought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…It is well known that under stressed conditions, carbohydrates can act as osmoprotectants that remove reactive oxygen species (ROS) and stabilise cellular membranes, which can protect plants from oxidative damage [ 44 ]. Under stressed conditions, several previous studies, such as those on poplar [ 41 ], Arabidopsis [ 23 ], maize [ 45 ] and potato [ 46 ], have shown that the application of biostimulants and organic amendments increases the expression of various proteins that often participate in energy and carbohydrate metabolism. These results suggest that enzymes associated with the glycolytic pathway might assist in the intensification of glycolysis to provide energy for supporting plant growth and metabolic activities under abiotic and biotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that under stressed conditions, carbohydrates can act as osmoprotectants that remove reactive oxygen species (ROS) and stabilise cellular membranes, which can protect plants from oxidative damage [ 44 ]. Under stressed conditions, several previous studies, such as those on poplar [ 41 ], Arabidopsis [ 23 ], maize [ 45 ] and potato [ 46 ], have shown that the application of biostimulants and organic amendments increases the expression of various proteins that often participate in energy and carbohydrate metabolism. These results suggest that enzymes associated with the glycolytic pathway might assist in the intensification of glycolysis to provide energy for supporting plant growth and metabolic activities under abiotic and biotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…The microbial consortium is a commercial product—Bacstim ® 100, containing equal volumes of the above-mentioned Bacillus strains (Omnia Group Ltd., South Africa). The biostimulant activity of this microbial consortium, Bacstim ® 100, has been tested on maize plants under greenhouse conditions, where enhanced plant growth and drought tolerance was demonstrated ( Nephali et al, 2021 ; Othibeng et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Other mechanisms associated with enhancing stress tolerance involve triggering biological and physiological processes such as ROS detoxification mechanisms, osmoprotection, stomatal regulation, membrane stability, xylem hydraulic conductance, root zone water, and nutrient availability and metal chelation [ 99 , 100 , 101 ]. For example, recent studies by Nephali et al [ 11 ], Lephatsi et al [ 13 ] and Othibeng et al [ 102 ] revealed that the application of Bacillus consortium (a commercial biostimulant known as Bacstim ® 100) to maize plants improves drought tolerance via mechanism such as enhanced energy production, enhanced expression of drought stress responsive defense genes, osmoregulation, redox homeostasis, strengthening of the plant cell wall and membrane remodeling.…”
Section: Bacillus Spp Confers Protection To the Plant From E...mentioning
confidence: 99%